Initiatives on language planning and policy taken by different agencies in Bangladesh: An analysis - Rahim, Abdur (Dhaka University Journal of Linguistics, 2009)
Language planning is a crying need for the development of Bangla Language. Different agencies like Bangla Academy, Universities, Education Ministry and Education Board, Bangladesh Asiatic Society and some other organizations have taken several initiatives in this regard. But unfortunately, these steps were not adequate enough as well an integral chain among the above mentioned organizations is yet to be established. As a result, the planning progress of Bangla is still hindered. In this paper, an attempt has been taken to compare the contributions of those institutions in Bangla language planning and to prepare a chronology of their initiatives. Dhaka University Journal of Linguistics Vol.1(1) 2008